A self-adhesive straw hot-pressed board based on hydrogen bond strengthening and a preparation method thereof

CN118682867BActive Publication Date: 2026-10-27HUADA ENTERPRISE HLDG LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410982877.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2026-10-27
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

[0005]此外,机械粉碎可以减少原料颗粒的尺寸,增加原料颗粒的比表面积,增强自胶粘能力,但是机械粉碎会导致加工成本增加、能耗提高的问题,因此机械粉碎通常与其他加工方法结合应用

Benefits of technology

[0011]本发明通过化学结构表征,研究了板材的自胶粘机理,既通过碱预处理去除小麦秸秆绝大部分木质素和部分半纤维素,使小麦秸秆的纤维素暴露出来,熔融盐对纤维素进行了润胀,使纤维素分子链上的羟基更多的暴露出来,在湿压热压工艺条件下,水和纤维素之间的氢键被纤维素羟基之间加强的氢键所替换,同时残留的锌离子作为催化剂或反应介质,进一步促进小麦秸秆纤维素之间通过加强氢键的自胶粘性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118682867B_ABST
    Figure CN118682867B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of self-adhesive straw hot-press plate based on hydrogen bond strengthening and its preparation method.The preparation method includes the following steps: (1) in alkaline solution, wheat straw is added to react, after reaction, filtration, washing, drying, and obtain the alkali pretreated wheat straw;(2) the alkali pretreated wheat straw is soaked in molten salt, and obtain the wet wheat straw, the wet wheat straw is treated by wet hot-pressing, and self-adhesive straw hot-press plate is prepared.The present application pretreats wheat straw with alkali, treats with molten salt, and introduces wet hot-pressing treatment, which can effectively enhance the physical and mechanical properties of self-adhesive wheat straw hot-press plate, has great research and development potential, and provides a more environmentally friendly and greener alternative for traditional biomass wood-based panels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional materials technology, specifically to a self-adhesive straw hot-pressed sheet based on hydrogen bond reinforcement and its preparation method. Background Technology

[0002] Wood-based panels are engineered wood products made by interweaving and gluing together wood fibers. Due to their excellent physical and mechanical properties and processing characteristics, they are widely used in furniture manufacturing, construction, and interior decoration. Traditionally, wood-based panels are one of the main products of wood processing. The production process consumes a large amount of timber, and long-term deforestation and clearing of forests have led to a reduction in forest area, limiting timber supply. At the same time, excessive logging also causes a series of problems such as environmental damage and deterioration. Furthermore, wood processing consumes a significant amount of energy. Therefore, there is an urgent need to find alternative raw materials.

[0003] Crop straw, rich in cellulose, hemicellulose, and lignin, holds promise as a primary raw material for replacing wood in the production of wood-based panels. Wheat, as one of the world's most widely distributed, largest-area, and second-highest-yielding grain crops, has wheat straw (natural wheat straw), an agricultural byproduct, possesses significant potential as a raw material for panels. However, the physical structure of minor components in wheat straw (such as waxes and pectin) reduces the compatibility and adhesion between straw particles. Furthermore, wheat straw has a rigid epidermal tissue rich in silicon. These characteristics result in poor self-adhesion in hot-pressed wheat straw panels.

[0004] Currently, researchers have discovered ways to add adhesives (such as formaldehyde resin) during the manufacturing process of boards to improve their various properties and strength. However, while adhesives such as urea-formaldehyde (UF), phenol-formaldehyde (PF), and melamine-urea-formaldehyde (MUF) adhesives can improve the physicochemical properties of boards, their use also has significant drawbacks: the boards release harmful substances such as formaldehyde during use, posing risks to human health and polluting the environment. Of course, researchers have also explored formaldehyde-free, green, natural adhesives, such as lignin adhesives, tannin adhesives, protein adhesives, and starch adhesives. However, the preparation of these natural adhesives is complex, and the raw materials are relatively expensive, leading to higher board manufacturing costs. Therefore, research on preparing adhesive-free boards through different pretreatment methods has garnered widespread attention.

[0005] Furthermore, mechanical pulverization can reduce the size of raw material particles, increase their specific surface area, and enhance their self-adhesive ability. However, mechanical pulverization leads to increased processing costs and energy consumption; therefore, it is usually combined with other processing methods. Xiao et al. studied the preparation of hot-pressed boards by treating reed straw with 2% NaOH, achieving a modulus of elasticity (MOE) of 2486 MPa and a flexural strength of 18.2 MPa. Tupciauskas et al. used wheat straw as raw material, steam-exploding it at 240°C for 1 min, and then preparing straw fiberboard at 175°C and 4 MPa. Their MOE and flexural strength reached 3840 MPa and 21 MPa, respectively. Yang et al. used wheat straw and bamboo straw fibers in different proportions as raw materials. First, they pretreated the boards with laccase at 50℃ for 120 min, then hot-pressed them at 170℃ and 4 MPa for 15 min. The optimal board performance was obtained when the laccase dosage was 40 U / g, with an elastic modulus (MOE) of 2743.83 MPa and a flexural strength of 18.88 MPa. The above research shows that pretreatment of straw can effectively change the surface morphology of raw lignocellulosic biomass, which is very effective in improving the performance of boards. However, how to provide self-adhesive straw hot-pressed boards with stronger stability has become a research hotspot. Therefore, this invention provides a hydrogen-bonded self-adhesive straw hot-pressed board and its preparation method. Summary of the Invention

[0006] The technical problem to be solved by this invention is to provide a self-adhesive straw hot-pressed sheet material based on hydrogen bond reinforcement and its preparation method. The aim is to provide a self-adhesive straw hot-pressed sheet material with stronger stability.

[0007] The technical solution of the present invention to solve the above-mentioned technical problems is as follows:

[0008] In a first aspect, a method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board includes the following steps:

[0009] (1) Add wheat straw to an alkaline solution to react. After the reaction is complete, filter, wash and dry to obtain alkaline pretreated wheat straw.

[0010] (2) The alkali-pretreated wheat straw is soaked in molten salt to obtain moist wheat straw. The moist wheat straw is then subjected to wet hot pressing to prepare a self-adhesive straw hot-pressed board.

[0011] This invention investigates the self-adhesive mechanism of boards through chemical structural characterization. Alkali pretreatment removes most of the lignin and some hemicellulose from wheat straw, exposing the cellulose. Molten salt swells the cellulose, further exposing the hydroxyl groups on the cellulose molecular chains. Under wet-press and hot-press conditions, the hydrogen bonds between water and cellulose are replaced by strengthened hydrogen bonds between the cellulose hydroxyl groups. Simultaneously, residual zinc ions act as a catalyst or reaction medium, further promoting the self-adhesive properties of wheat straw cellulose through enhanced hydrogen bonding.

[0012] The beneficial effects of the present invention are: (1) The present invention pre-treats wheat straw with alkali, treats it with molten salt, and introduces wet hot pressing treatment, which can effectively enhance the physical and mechanical properties of self-adhesive wheat straw hot pressing boards. It has great research and development potential and provides a more environmentally friendly and greener alternative to traditional biomass wood boards.

[0013] (2) This invention provides a new approach for the high-value utilization of agricultural by-products and demonstrates the potential for preparing environmentally friendly biomass boards. By enhancing the effect of hydrogen bonds, high-performance boards can be prepared without traditional chemical adhesives, which are environmentally friendly and low-cost, and help promote the development of sustainable materials.

[0014] Wet hot pressing refers to hot pressing the raw materials while maintaining a certain moisture content. On the one hand, water can act as a flow agent, allowing small particles to effectively fill the gaps between large particles during the compression molding process. This results in a more uniform and denser structure in the finished board, thereby effectively improving the dimensional stability and mechanical strength of the board. On the other hand, water can act as a heat medium, allowing the raw materials to be heated more evenly during the hot pressing process, thus avoiding local overheating.

[0015] Based on the above technical solution, the present invention can be further improved as follows.

[0016] Furthermore, the molten salt in step (2) includes at least one of zinc chloride molten salt, aluminum trichloride molten salt, and cuprous chloride molten salt; the molten salt is prepared by dissolving zinc chloride, aluminum trichloride, and / or cuprous chloride in water.

[0017] The beneficial effect of adopting the above-mentioned further scheme is that the hydrogen bonds between cellulose in the lignin-free straw are destroyed by molten salt, so that the hydroxyl groups on the surface can be fully released.

[0018] The mass concentration of the zinc chloride molten salt in step (2) is 65%.

[0019] The beneficial effect of adopting the above-mentioned further scheme is that the zinc chloride molten salt with a mass concentration of 65% forms ZnCl2·2.33H2O molten salt.

[0020] Furthermore, the zinc chloride molten salt in step (2) is prepared by dissolving zinc chloride in water.

[0021] Furthermore, in step (2), the mass-to-volume ratio of the alkali-pretreated wheat straw to the zinc chloride molten salt is 1 g: (5-20) mL;

[0022] The soaking parameters in step (2) are: soaking for 24 to 48 hours under normal temperature and pressure conditions;

[0023] The parameters for wet hot pressing in step (2) are: pressure of 15MPa to 20MPa, temperature of 60℃ to 80℃, and time of 2h to 6h.

[0024] Furthermore, the parameters for wet hot pressing in step (2) are: pressure of 15 MPa, temperature of 80 °C, and time of 4 h.

[0025] The beneficial effect of adopting the above-mentioned further solution is that, through wet hot pressing, the hydroxyl groups on the surface of cellulose that have been broken by molten salt are recombined and new hydrogen bonds are generated.

[0026] Furthermore, the solute in the alkaline solution in step (1) includes at least one of NaOH, Na2SO3, and Ca(OH)2.

[0027] The beneficial effects of adopting the above-mentioned further solution are: the present invention can remove lignin from straw by using an alkaline solution, thereby exposing cellulose and hemicellulose.

[0028] Furthermore, the solutes in the alkaline solution in step (1) include NaOH and Na2SO3; the concentration of NaOH in the alkaline solution is 2M to 5M, for example, 2M, 2.5M, 5M, etc.; the concentration of Na2SO3 in the alkaline solution is 0.25M to 1M, for example, 0.25M, 0.5M, 1M, etc.

[0029] Furthermore, the mass-to-volume ratio of the wheat straw to the alkaline solution in step (1) is (0.5-2) g: (5-20) mL, for example, 1 g: 10 mL, etc.

[0030] The reaction parameters in step (1) are: temperature of 80℃~100℃, such as 80℃, 95℃, 100℃, etc., and time of at least 4h;

[0031] The moisture content of the wheat straw pretreated with alkali in step (1) is less than 4%.

[0032] Secondly, a hydrogen bond-reinforced self-adhesive straw hot-pressed board is provided, wherein the hydrogen bond-reinforced self-adhesive straw hot-pressed board is prepared by the aforementioned preparation method.

[0033] Furthermore, the hydrogen bond-reinforced self-adhesive straw hot-pressed sheet has a tensile strength of 8.42 MPa, an internal bonding strength of 0.749 MPa, a flexural strength of 20.366 MPa, and a flexural modulus of 2.663 GPa. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the preparation method of the hydrogen bond-reinforced self-adhesive straw hot-pressed board of the present invention;

[0035] Figure 2 The mechanical properties of different sheet materials of the present invention are as follows: (a) tensile strength; (b) internal bond strength; (c) flexural strength and flexural modulus.

[0036] Figure 3 The chemical structure diagrams of different plates of the present invention are shown below; (a) and (b) FTIR spectra; (c) chemical composition content diagram; (d) XPS spectrum; (e) high-resolution C1s XPS spectrum; (f) XRD spectrum.

[0037] Figure 4 This is a graph showing the hydroxyl content of different materials used in this invention;

[0038] Figure 5 The images show the microstructures of different substrate surfaces of the present invention: (a) WS; (b) WS-A; (c) WS-A-Zn-2.

[0039] Figure 6 Thermogravimetric analysis of different plates for this invention includes (a) TG analysis and (b) DTG analysis.

[0040] Figure 7 This is a diagram illustrating the self-adhesive mechanism of the wheat straw hot-pressed sheet of the present invention. Detailed Implementation

[0041] The principles and features of this invention are described below. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they should be performed according to the techniques or conditions described in the literature in this field, or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.

[0042] The following description of the sources of materials and reagents used in the examples:

[0043] Wheat straw was collected from a farm in Urumqi. It was first crushed, then repeatedly washed with clean water, and finally sieved using a laboratory sieve to obtain particles between 3.0 mm and 5.0 mm in size as experimental material. The sieve was then dried at 105℃ for 12 hours and stored in a sealed bag for further use. Sodium hydroxide, anhydrous sodium sulfite, and anhydrous zinc chloride were purchased from InnoChem Chemical Reagent Co., Ltd. (China). Deionized water was prepared using a WPUP-UV-20 instrument from Chengdu Water Technology Co., Ltd. (Sichuan). All reagents were used directly without further purification after purchase.

[0044] 1. Experimental methods.

[0045] This embodiment relates to a method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board, which includes the following steps:

[0046] (1) Add wheat straw to an alkaline solution to react. After the reaction is complete, filter, wash and dry to obtain alkaline pretreated wheat straw.

[0047] (2) The alkali-pretreated wheat straw was soaked in zinc chloride molten salt to obtain moist wheat straw. The moist wheat straw was then subjected to wet hot pressing to prepare self-adhesive straw hot-pressed boards. The experimental procedure is as follows: Figure 1 As shown.

[0048] In this preferred embodiment, a method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board includes the following specific steps:

[0049] (1) Alkali pretreatment of wheat straw: First, weigh 50g of sodium hydroxide and 25g of anhydrous sodium sulfite, prepare 500ml of a mixed solution of 2.5M NaOH and 0.5M Na2SO3, pour it into a round-bottom flask, weigh 50g of wheat straw that has been dried and sealed in a bag according to a solid-liquid ratio of 1:10, heat it in a 95℃ water bath for 4h, then filter the obtained product and wash it with deionized water until the pH of the filtrate is neutral. The obtained alkali-pretreated wheat straw is dried in an oven at 105℃ for 12h to reduce its moisture content to below 4%, and stored in a sealed bag for further use.

[0050] (2) Zinc chloride treatment of wheat straw: First, weigh 65g of anhydrous zinc chloride and dissolve it in 100ml of deionized water to prepare a 65% (wt%) zinc chloride molten salt. Weigh 10g of previously dried alkali-pretreated wheat straw and soak it at room temperature for 20h to obtain moist wheat straw. After filtering and washing, the moistened wheat straw is directly placed into a 50mm×50mm×5mm hot press mold for wet hot pressing to prepare self-adhesive straw hot press board (WS-A-Zn).

[0051] (3) The moist wheat straw was directly placed into a 50mm×50mm×5mm hot press mold. Using a single variable method, that is, for the three variables of hot pressing pressure, temperature and time, only one hot pressing process condition was changed, while the other two hot pressing process conditions were kept constant. The effects of hot pressing time, temperature and pressure on the performance of hot-pressed boards made of zinc chloride-treated wheat straw were studied. Different hot pressing process parameters are shown in Table 1. Hot pressing was carried out at different temperatures (60℃, 80℃, 100℃), pressures (10MPa, 15MPa, 20MPa) and times (2h, 4h, 6h) to determine the optimal hot pressing process conditions. Self-adhesive wheat straw hot-pressed boards prepared by the above-mentioned moist wheat straw after filtration and washing (WS-Wash), alkali pre-treated wheat straw (WS-A) only, and untreated wheat straw (WS) under the same hot pressing process conditions were used as parallel control experiments.

[0052] Table 1 Hot-pressing process parameters for self-adhesive wheat straw hot-pressed boards

[0053]

[0054] 2. Performance testing.

[0055] 2.1 Mechanical property testing.

[0056] According to GB / T 11718-2013, an STX1000 digital display single-arm micro-controlled electronic universal testing machine was used. For each group of samples (WS-A-Zn-2, WS-Wash, WS-A, and WS), five replicates of tensile strength, flexural strength, flexural modulus, and internal bond strength (IB) were tested, and the average value was calculated. Tensile and flexural strength tests were performed on samples with dimensions of 50±1×50±1×5.0 mm. Internal bond strength tests were also performed on samples with dimensions of 50±1×50±1×5.0 mm. The specimens were effectively bonded to the chuck with hot melt adhesive, which was fully cured before the tension test.

[0057] 2.2 Morphological analysis of the sheet material.

[0058] The WS-A-Zn-2 sample with the best mechanical strength, along with the parallel control samples WS-A and WS, were dried and fixed to the sample stage with carbon tape. The samples were then coated with gold under vacuum and placed in the sample chamber of an environmental scanning electron microscope (Quanta200, FEI). With the voltage set to 15 kV, imaging parameters adjusted, magnification increased to 200x, and a suitable field of view selected, the surface of the plate samples was observed, and the images were recorded and stored.

[0059] 2.3 Water Absorption Rate (WA) Test.

[0060] The WS-A-Zn-2 sample with the best mechanical strength, along with the parallel control samples WS-A and WS, were cut into standard samples with dimensions of 10±1×10±1 mm, and their weights were measured. According to the Chinese standard (China Wood Industry Research Institute, CAF, 2013), the equilibrated samples were soaked in water at room temperature for 24 hours, the water droplets on the sample surface were wiped off with a towel, and the samples were weighed. Five replicates were tested for each group of samples, and the average water absorption rate was calculated.

[0061] 2.4 Chemical structure characterization.

[0062] Chemical structure characterization was performed on the WS-A-Zn-2 sample exhibiting the best mechanical strength, as well as on parallel control samples WS-A and WS. Fourier transform infrared spectroscopy (FTIR) was performed using a Thermo Scientific iN10 spectroscopy system, with a wavenumber range of 600 cm⁻¹. -1 -4000cm -1 Within the specified range, absorbance testing mode was used.

[0063] X-ray photoelectron spectroscopy (XPS) was performed using Thermo Scientific K-Alpha, a 150W single-chromium Al Kα (hv = 1486.6 eV) X-ray source. The chemical composition of the substrate was determined according to the procedures of the National Renewable Energy Laboratory (NREL).

[0064] X-ray diffraction (XRD) was performed using a Rigaku SmartLab SE laser from Japan, employing a Cu Kα radiation source. The scanning angle ranged from 5° to 40°, and the scanning speed was 2° / min. The crystallinity index (CrI) was calculated using the Segal equation, and the formula is as follows:

[0065] CrI%=((I 200 -I am ) / I 200 )×100 (1)

[0066] In the formula, CrI is the crystallinity index, and I... 200 The maximum intensity of the peak near 2θ = 22.5°, I am The minimum intensity between the (200) and (110) peaks (around 2θ = 18°) is the crystallinity, which represents the proportion of amorphous cellulose.

[0067] The hydroxyl content in the board samples was determined by polyester polyol titration. The titration instrument used was a Metrohm 916Ti-Touch from Switzerland.

[0068] 2.5 Thermogravimetric analysis (TGA).

[0069] The thermal stability of the plates was tested and analyzed using thermogravimetric analysis (TGA). Each sample (ca.5 mg) was heated at a rate of 300 mL / min with nitrogen gas (purity >99.9999 vol%) at a rate of 5 °C / min, with a test temperature range of 30–700 °C. The TGA was performed using a Hitachi High-Tech Scientific Model (STA7200).

[0070] 3. Results and Discussion.

[0071] 3.1 Mechanical property analysis.

[0072] Different mechanical properties of boards, such as Figure 2 As shown. Through analysis Figure 2 (a) shows the tensile strength of the sheet metal, indicating that the WS-A-Zn-2 sample exhibits the best tensile strength, reaching 8.42 MPa. Analysis... Figure 2 (b) The internal bond strength of the plates shows that the WS-A-Zn-2 sample has the best internal bond strength, reaching 0.749 MPa. Through analysis... Figure 2 (c) The bending strength and bending modulus of the sheet metal show that the WS-A-Zn-2 sample has the best bending strength and bending modulus, with a bending strength of 20.366 MPa and a bending modulus of 2.663 GPa.

[0073] Analysis of the mechanical properties of different boards revealed that the self-adhesive wheat straw hot-pressed board treated with ZnCl2 but not filtered or washed achieved the best mechanical properties under the following conditions: hot-pressing pressure of 15 MPa, hot-pressing temperature of 80℃, and hot-pressing time of 4 h. This is because when the hot-pressing pressure is too low (10 MPa), water cannot flow effectively between the wheat straw fibers, preventing small particles from uniformly filling the gaps between large particles. This results in uneven density distribution of the board, preventing the exposed hydroxyl groups of the wheat straw after ZnCl2 treatment from fully bonding to form hydrogen bonds, thus reducing the self-adhesive properties of the board. Conversely, when the hot-pressing pressure is too high (above 20 MPa), it leads to wheat straw fiber breakage and excessive compression, disrupting the hydrogen bonds between the cellulose hydroxyl groups of the wheat straw, causing the board to become brittle and hard, thereby reducing its mechanical properties. When the hot-pressing temperature is too low (below 60℃), because this invention uses a wet hot-pressing process, the low temperature cannot fully evaporate the moisture in the raw materials. The hydrogen bonds between the hydroxyl groups in water and cellulose cannot be fully replaced by the hydrogen bonds between the exposed hydroxyl groups of cellulose, hindering the self-adhesive bonding between wheat straw fibers. When the hot-pressing temperature is too high (above 100℃), because the ZnCl2 molten salt is acidic, the cellulose and hemicellulose in the alkali pretreated wheat straw are hydrolyzed into monosaccharides, such as glucose and xylose, under high temperature and acidic conditions. The monosaccharides further undergo dehydration reactions to form furfural, which greatly reduces the content of cellulose and its exposed hydroxyl groups, resulting in a significant decrease in the strength of the hydrogen bonds formed between the hydroxyl groups, thus reducing the performance and strength of the board. When the hot-pressing time is too short (less than 2 hours), the hydrogen bonds between the hydroxyl groups in water and cellulose are not fully replaced by the hydrogen bonds between the exposed hydroxyl groups in cellulose, resulting in a decrease in the adhesive force between wheat straw cellulose fibers, thereby reducing the mechanical strength of the board. When the hot-pressing time is too long (more than 6 hours), the lignin in the wheat straw flows excessively, destroying the hydrogen bonds between the hydroxyl groups in the wheat straw cellulose, leading to an increase in the internal stress of the board, thereby reducing the mechanical properties of the board.

[0074] Meanwhile, under the same hot-pressing conditions, the mechanical properties of the WS-A-Zn-2 sample were significantly greater than those of the WS-Wash, WS, and WS-A samples. This is because: firstly, after alkali pretreatment, most of the lignin, some hemicellulose, and impurities in the wheat straw were removed, exposing a large amount of cellulose. Further treatment with ZnCl2 molten salt further swelled the cellulose in the wheat straw, exposing a large number of hydroxyl groups. During hot pressing, the hydrogen bonds between water and cellulose were replaced by hydrogen bonds between cellulose hydroxyl groups, which greatly enhanced the mechanical properties of the board. Secondly, the residual zinc ions acted as a catalyst, promoting the cross-linking reaction between polysaccharides (mainly cellulose and hemicellulose) and lignin in the wheat straw. This cross-linking reaction formed more chemical bonds during hot pressing, enhancing the self-adhesive properties of the board. 3.2 Chemical Structure Analysis.

[0075] FTIR characterization can be used to obtain information about the functional groups of materials. The FTIR spectra of different substrates are shown below. Figure 3 As shown in (a) and (b), WS-A-Zn-2, WS-A, and WS samples were stored at 3338 cm⁻¹. -1 and 3400cm -1 A broad peak at position 1 indicates the presence of an OH bond, a characteristic of alcohols and phenols, representing the abundant cellulose component in wheat straw. The OH peak in the WS-A-Zn-2 sample shifts to a lower wavenumber compared to the WS-A and WS samples. This is because the stretching vibration frequency of the hydroxyl group (-OH) changes during hydrogen bond formation, particularly with hydrogen bond enhancement, leading to a decrease in the OH peak's stretching vibration frequency and a shift to a lower wavenumber. This confirms the hydrogen bond enhancement mechanism based on hydroxyl groups in this invention. A peak at 2903 cm⁻¹... -1 The peak intensity at this location indicates that the symmetric stretching vibration of the CH bond in the alkyl group is caused by the CH bond vibration of the alkyl chain in hemicellulose. The significantly weakened peak intensity at this location in the WS-A-Zn-2 sample suggests that ZnCl2 treatment caused some CH bonds to react and transform into other chemical structures, resulting in a weakened absorption peak intensity. At 1740 cm⁻¹ -1 The absorption peak at 1740 cm⁻¹ is due to the stretching vibrations of acetyl groups and C=O in hemicellulose. Compared with the WS sample, the WS-A-Zn₂ and WS-A samples show a higher absorption peak at 1740 cm⁻¹. -1 The absorption peak intensity decreased significantly, indicating that alkali pretreatment caused degradation of impurities such as hemicellulose and protein to some extent. Meanwhile, the WS-A-Zn-2 sample showed a significantly lower absorption peak intensity at 1630 cm⁻¹. -1 A very obvious absorption peak appears at 1162 cm⁻¹, which is caused by the symmetric stretching vibration of the carbonyl group (C=O) of the carboxylate. This indicates that the residual zinc ions act as a catalyst or reaction medium, promoting the deprotonation of certain carboxylic acids and their subsequent binding with zinc ions to form carboxylate salts, thus resulting in a strong absorption peak at this point. -1 and 1062cm -1The absorption peaks at these locations are related to the stretching vibrations of the COC and CO bonds in polysaccharides (such as cellulose) in wheat straw. The WS-A-Zn-2 sample showed significantly enhanced absorption peak intensities at these locations, indicating that ZnCl2 treatment swelled the cellulose exposed in the wheat straw after alkali pretreatment, resulting in a significant increase in peak intensity. Spectroscopic analysis revealed that alkali pretreatment removed some impurities such as lignin, hemicellulose, and protein from the wheat straw, exposing more cellulose. ZnCl2 treatment then swelled the exposed cellulose, exposing more hydroxyl groups. Under wet pressure and hot-pressing conditions at 80℃, 15MPa, and 4h, the hydrogen bonds between water and cellulose were replaced by hydrogen bonds between cellulose hydroxyl groups, thus strengthening the hydrogen bonds.

[0076] The chemical composition content of different boards, such as Figure 3 As shown in (c), comparing the chemical composition diagrams of the WS samples reveals that the lignin and hemicellulose contents decreased in the WS-A and WS-A-Zn-2 samples. This is because alkali pretreatment removed most of the lignin, some hemicellulose, and impurities from the wheat straw. Conversely, the impurity content increased in the WS-A-Zn-2 sample, likely due to the presence of zinc ions. Analysis of the chemical composition diagrams for different boards shows that alkali pretreatment degraded most of the lignin and some of the hemicellulose in the wheat straw, while ZnCl2 treatment had little effect on the cellulose, hemicellulose, and lignin contents. These changes in chemical composition are in good agreement with the FTIR spectra.

[0077] XPS characterization is a technique used to analyze the chemical composition of substrate surfaces. XPS spectra of different substrates are shown below. Figure 3 As shown in (d), the O / C value of the WS-A sample surface is 0.5, significantly higher than the O / C values ​​of the WS sample surface (0.31) and the WS-A-Zn-2 sample surface (0.32). This is because alkali pretreatment leads to a decrease in the concentration of lignin and hemicellulose in wheat straw, exposing the cellulose on the WS-A sample surface. Cellulose has more hydroxyl groups (-OH) than hemicellulose and lignin, thus significantly increasing the O / C value of the WS-A sample. Interestingly, however, the O / C value of the board sample surface actually decreases after ZnCl2 treatment. This is because, in addition to the alkali pretreatment exposing more cellulose, ZnCl2 molten salt treatment further swells the cellulose, exposing more hydroxyl groups. Under wet pressing and hot pressing conditions, the hydrogen bonds between water and cellulose are replaced by hydrogen bonds between cellulose hydroxyl groups. Furthermore, the residual zinc chloride acts as a catalyst or reaction medium, forming a carbon-based cross-linked structure, thereby reducing the O / C value. High-resolution C1s XPS spectra are shown below. Figure 3As shown in (e), the four C atoms in the spectrum, C1-C4, are as follows: C1: CH, CC; C2: CO; C3: C=O, OCO; C4: OC=O. Analysis reveals that the C1 peak component, representing lignin and extract, in the WS-A sample spectrum is significantly lower than that in the WS sample, while the C2 peak component in the WS-A sample spectrum is significantly higher than that in the WS group samples. This is because alkali pretreatment removes most of the lignin and some hemicellulose from wheat straw, thus decreasing the C1 peak component in the WS-A sample. Alkali pretreatment exposes more cellulose in the wheat straw, and since cellulose is rich in CO bonds, the C2 peak component in the WS-A sample increases. However, the C2 peak of the WS-A-Zn-2 sample decreased. This is because, after the alkali pretreatment exposed more cellulose, the ZnCl2 treatment further swelled the cellulose, exposing more hydroxyl groups. Under the wet pressing and hot pressing process, the hydrogen bonds between water and cellulose were replaced by hydrogen bonds between cellulose hydroxyl groups. On the other hand, the residual zinc chloride acted as a catalyst or reaction medium, forming a carbon-based cross-linked structure. Therefore, the C2 peak component content of the WS-A-Zn-2 sample decreased, which is consistent with the O / C analysis results.

[0078] XRD characterization analysis can yield information about the crystal structure of the substrate. XRD patterns of different substrates are shown below. Figure 3 As shown in (f), there are obvious peaks around 15.8°, 22.5°, and 34.7°, corresponding to the (110), (200), and (004) lattice planes, respectively, which is typical of cellulose I. The CrI value of the WS-A-Zn-2 sample is 59.2%, which is higher than that of the WS-A sample (53.3%) and the WS sample (43.6%). This is because the alkali pretreatment removes most of the lignin and some hemicellulose from the wheat straw board, thereby exposing the cellulose, which helps the cellulose to rearrange and partially crystallize. The ZnCl2 treatment causes the exposed cellulose to swell, increasing the number of hydroxyl groups on the cellulose surface. During the hot pressing process, the hydrogen bonds between water and cellulose are replaced by the enhanced hydrogen bonds between the cellulose hydroxyl groups, promoting the rearrangement of hydrogen bonds to form a more compact molecular stacking structure, which further improves the crystallinity of the board and thus enhances the performance and strength of the board.

[0079] Hydroxyl content of different boards, such as Figure 4As shown in the figure, the hydroxyl content analysis reveals that the hydroxyl content of the WS-A-Zn-2 sample is lower than that of the WS-A and WS samples, reaching only 15.26 mg KOH / g. This is because the ZnCl2 treatment causes the cellulose exposed after alkali pretreatment to swell, exposing a large number of hydroxyl groups. Under the wet pressing hot pressing process, the hydrogen bonds between water and cellulose are replaced by the strengthened hydrogen bonds between cellulose hydroxyl groups. Since the hydroxyl groups are bound by the strengthened hydrogen bonds, they do not react with KOH, resulting in an extremely low measured hydroxyl content, which is consistent with the experimental results of this invention.

[0080] 3.3 Analysis of the surface morphology of the sheet material.

[0081] Microstructures of different board surfaces, such as Figure 5 As shown. By observation Figure 5 (a) It can be seen that the wheat straw fibers on the surface of the WS sample remain in their natural state, with a rough and uneven surface texture and a large number of irregular pores. Through observation and comparison... Figure 5 (b) As can be seen from the WS sample, the cellulose on the surface of the WS-A sample is more exposed, the porosity between fibers increases, the degree of fiber dispersion increases, and more fiber separation occurs on the surface, showing a uniform and compact fiber arrangement. This is because the alkali pretreatment removes most of the lignin, some hemicellulose, and impurities such as protein and pectin from the wheat straw, thereby improving the adhesion between fibers. And through... Figure 5 (c) The WS-A-Zn-2 sample shows that wheat straw was fully swollen after alkali pretreatment to expose cellulose, exposing more hydroxyl groups. The enhanced hydrogen bonding between the hydroxyl groups of cellulose significantly improved the self-adhesiveness of the board.

[0082] 3.4 Thermogravimetric analysis.

[0083] Thermogravimetric analysis (TGA) can be used to reflect the thermal stability and thermal decomposition properties of materials. Examples of TGA analyses for different sheet materials include... Figure 6 As shown. By Figure 6As shown in the TG curve of (a), unlike the single thermal decomposition process of WS and WS-A samples, the WS-A-Zn-2 sample exhibits a complex thermal decomposition process, which mainly consists of three stages. The first stage occurs at 80℃, where the bound water and adsorbed water contained in the board evaporate. The second stage occurs at 230℃, due to the thermal degradation of lignin, cellulose, and hemicellulose. The final pyrolysis stage occurs at 540℃, where the residual ZnCl2 in the WS-A-Zn-2 sample pyrolyzes to form zinc chloride gas (ZnCl2) and chlorine gas (Cl2). It can be observed that the weight loss rate of the WS-A-Zn-2 sample is much smaller than that of the WS-A and WS samples. This is because the cellulose fibers achieve self-adhesion through hydrogen bonds strengthened by hydroxyl groups, which significantly improves the thermal stability of the board.

[0084] Figure 6 (b) DTG analysis shows that the maximum degradation rate of sample WS-A is higher than that of samples WS and WS-A-Zn-2. Therefore, sample WS-A-Zn-2 exhibits the best thermal stability and resistance to thermal degradation during combustion. This is because alkali pretreatment removes most of the lignin and some hemicellulose from wheat straw. These components have high thermal stability. After removing these components, the proportion of cellulose in the board increases relatively. Since the thermal degradation of cellulose usually occurs within a narrow temperature range, it is reflected in a higher maximum degradation rate on the DTG curve. The strong hydrogen bonding between cellulose molecules and the residual zinc chloride in sample WS-A-Zn-2 significantly improve its thermal stability. Thermogravimetric analysis shows that sample WS-A-Zn-2 has better thermal stability compared to samples WS-A and WS.

[0085] 3.5 Self-adhesive mechanism of wheat straw hot-pressed boards based on hydrogen bond reinforcement and wet pressing process.

[0086] Compared with traditional boards that have adhesives applied, the self-adhesive wheat straw hot-pressed board proposed in this invention, based on hydrogen bond reinforcement and wet pressing process, does not require the addition of adhesives and has good mechanical properties.

[0087] Board bonding mechanism, such as Figure 7 As shown in the diagram, the process begins with alkali pretreatment to remove most of the lignin and some of the hemicellulose from the wheat straw, exposing the cellulose that was previously covered by hemicellulose and lignin. ZnCl2 molten salt treatment further swells the exposed cellulose, fully exposing the hydroxyl groups on the cellulose surface. Under wet-press and hot-press conditions, the hydrogen bonds between water and cellulose are replaced by stronger hydrogen bonds between the cellulose hydroxyl groups. The remaining zinc ions act as a catalyst or reaction medium, further promoting the self-adhesion between wheat straw cellulose fibers through strengthened hydrogen bonds. This results in a more stable, denser, and stronger microstructure in the wheat straw board.

[0088] 4. Conclusion.

[0089] The preparation of self-adhesive wheat straw hot-pressed board based on hydrogen bond reinforcement and wet pressing process of the present invention includes the following research conclusions:

[0090] (1) Based on the alkali pretreatment of wheat straw, the present invention further treats it with 65% (wt%) ZnCl2 molten salt and adopts a wet pressing hot pressing process. The optimal hot pressing process parameters were investigated and it was found that the prepared board has the best mechanical properties when hot pressing at 80℃, 15MPa and 4h.

[0091] (2) This invention investigates the mechanism of ZnCl2 treatment to enhance self-adhesive wheat straw hot-pressed boards. The study found that after alkali pretreatment removes most of the lignin and some hemicellulose from the wheat straw, exposing the cellulose, ZnCl2 molten salt swells the exposed cellulose, exposing more hydroxyl groups on the cellulose molecular chains. Under wet-press hot-pressing conditions, the hydrogen bonds between water and cellulose are replaced by enhanced hydrogen bonds between cellulose hydroxyl groups. The residual zinc ions act as a catalyst or reaction medium, further promoting the self-adhesive properties of wheat straw cellulose through enhanced hydrogen bonds, thereby improving the strength of the self-adhesive wheat straw hot-pressed boards.

[0092] In summary, this invention demonstrates that alkali pretreatment and molten salt treatment of wheat straw can effectively enhance the physical and mechanical properties of self-adhesive wheat straw hot-pressed boards, showing great research and development potential and providing a more environmentally friendly and greener alternative to traditional biomass wood-based panels.

[0093] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a self-adhesive straw hot-pressed board based on hydrogen bond reinforcement, characterized in that, Includes the following steps: (1) Add wheat straw to an alkaline solution to react. After the reaction is complete, filter, wash and dry to obtain alkaline pretreated wheat straw. (2) The alkali-pretreated wheat straw is soaked in molten salt to obtain moist wheat straw, and the moist wheat straw is subjected to wet hot pressing to prepare self-adhesive straw hot pressing board. The molten salt mentioned in step (2) is zinc chloride molten salt; The parameters for wet hot pressing in step (2) are: pressure of 15MPa to 20MPa, temperature of 60℃ to 80℃, and time of 2h to 6h. The mass concentration of the zinc chloride molten salt mentioned in step (2) is 65%; The mass-to-volume ratio of the alkali-pretreated wheat straw to the zinc chloride molten salt in step (2) is 1 g: (5-20) mL; The soaking parameters in step (2) are: soaking for 24 to 48 hours under normal temperature and pressure conditions; The mass-to-volume ratio of wheat straw to alkaline solution in step (1) is (0.5-2) g : (5-20) mL; The reaction parameters in step (1) are: temperature 80℃~100℃, time at least 4h; In step (1), the product obtained after the reaction is completed is filtered and washed with deionized water until the pH of the filtrate is neutral. The obtained alkali pretreated wheat straw is dried until the moisture content is less than 4%.

2. The method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board according to claim 1, characterized in that, The molten salt is prepared by dissolving zinc chloride in water.

3. The method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board according to claim 1, characterized in that, The parameters for wet hot pressing in step (2) are: pressure 15MPa, temperature 80℃, and time 4h.

4. The method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board according to claim 1, characterized in that, The solute in the alkaline solution in step (1) includes at least one of NaOH, Na2SO3, and Ca(OH)2.

5. The method for preparing a hydrogen-bonded self-adhesive straw hot-pressed board according to claim 4, characterized in that, The solutes in the alkaline solution in step (1) include NaOH and Na2SO3; the concentration of NaOH in the alkaline solution is 2M to 5M; and the concentration of Na2SO3 in the alkaline solution is 0.25M to 1M.

6. A self-adhesive straw hot-pressed board material based on hydrogen bond reinforcement, characterized in that, The hydrogen bond-reinforced self-adhesive straw hot-pressed board is prepared by the preparation method according to any one of claims 1 to 5.

7. The self-adhesive straw hot-pressed board material based on hydrogen bond reinforcement according to claim 6, characterized in that, The hydrogen bond-reinforced self-adhesive straw hot-pressed sheet has a tensile strength of 8.42 MPa, an internal bonding strength of 0.749 MPa, a flexural strength of 20.366 MPa, and a flexural modulus of 2.663 GPa.

Citation Information

Patent Citations

  • Synchronization method for preparing microfibrillated cellulose and application of microfibrillated cellulose in strengthening of paper

    CN104562823A

  • Method for preparing surface-activated straw-based porous activated carbon

    CN107804848A

  • Gentle and rapid lignin separation method

    CN110527111A

  • Adhesive-free fiberboard and preparation method thereof

    CN117464800A

  • Method for bonding wood without glue under room temperature micro pressure and application

    CN118081915A